2019
DOI: 10.1016/j.neulet.2019.03.038
|View full text |Cite
|
Sign up to set email alerts
|

Association of variants of prodynorphin promoter 68-bp repeats in caucasians with opioid dependence diagnosis: Effect on age trajectory of heroin use

Abstract: The dynorphin/kappa opioid receptor (Dyn/KOR) system is involved in reward processing and dysphoria/anhedonia. Exposure to mu-opioid receptor agonists such as heroin increases expression of the prodynorphin gene (PDYN) in the brain. In this study in a Caucasian cohort, we examined the association of the functional PDYN 68-bp repeat polymorphism with opioid use disorders. In this case-control study, 554 subjects with Caucasian ancestry (142 healthy controls, 153 opioidexposed, but never opioid dependent, NOD an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 36 publications
1
1
0
Order By: Relevance
“…A second group of gene variants that have been shown to be associated with different addictive diseases is the functional 68–base pair (bp) repeat present in one to four copies in the promoter of the prodynorphin ( PDYN ) gene, which encodes for the endogenous neuropeptide at κ-opioid receptors ( 94 ). Some studies have found an association of this polymorphism with aspects of opioid addiction ( 95 , 96 ) in Caucasian populations, and similar findings of association of the number of 68-bp repeats have been reported in studies of the genetic determinants of cocaine addiction ( 97 ).…”
Section: Current Treatment For Opioid Addictionsupporting
confidence: 79%
“…A second group of gene variants that have been shown to be associated with different addictive diseases is the functional 68–base pair (bp) repeat present in one to four copies in the promoter of the prodynorphin ( PDYN ) gene, which encodes for the endogenous neuropeptide at κ-opioid receptors ( 94 ). Some studies have found an association of this polymorphism with aspects of opioid addiction ( 95 , 96 ) in Caucasian populations, and similar findings of association of the number of 68-bp repeats have been reported in studies of the genetic determinants of cocaine addiction ( 97 ).…”
Section: Current Treatment For Opioid Addictionsupporting
confidence: 79%
“…First, the present outcomes were based on unadjusted estimates. Because raw data for confounding factors like age [30], gender [15], socioeconomic status [31] of the participants were unavailable, we could not perform the corresponding stratification analysis. Second, the number of participants of each included study was limited, thus lacking enough statistic power to guarantee the association.…”
Section: Study Limitationsmentioning
confidence: 99%